(untitled) (Journal of Science & Technology, 2022)
Crises expose organizational weaknesses, disrupt established norms, and pressure leaders to make urgent decisions. Although traditional crisis approaches focus on stabilization and loss control, new perspectives suggest that disruption can become a catalyst for systemic renewal. This research article introduces Project Alchemy, a concept describing how a crisis can be transformed into a strategic advantage through adaptive leadership, experimental project management, and capability building practices. A four phase model illustrates how leaders convert crisis constraints into enduring strengths. Realistic organizational data are provided through numerical tables showing measurable improvements in innovation, resilience, and employee outcomes. This research proposes that the organizations most likely to thrive are those that treat crises as raw material for reinvention rather than as an interruption requiring restoration.